The Effect of the Traditional Game naned Betengtengan towards Corner Learning in Sprint Athletics Material at SMP Negeri 4 Koto Baru - Devi Seftiyanti; Dian Estu Prasetyo; Maldin Ahmad Burhan (The Future of Education Journal, 2024)
This research was motivated by the results of observations made by the author, stating that the problem encountered was the students' low ability when sprinting on athletics material. Therefore, researchers conducted research on the influence of the traditional game Bebentengan on learning sprint athletics at SMPN 4 Koto Baru. The aim of this research is to find out how much influence the traditional game Bentengengan has on learning PJOK in sprint athletics material. This research uses quantitative research methods. The research design used is a pre-experimental design in the form of a one-group pretest-posttest design. The results of research on the influence of the traditional game Betengengan on the pre-test normality test show 0.719 > 0.05, so the data is normally distributed. Meanwhile, the post-test significant value shows 0.700 > 0.05, so the data is normally distributed. In hypothesis testing, the results can be seen that the sig (2-tailed) is 0.000 < 0.05, so it can be concluded that there is a real difference between sprinting ability after and before being treated with the traditional fortification game